Antinociception of petroleum ether fraction derived from crude methanol extract of Melastoma malabathricum leaves and its possible mechanisms of action in animal models - Zakaria, Zainul Amiruddin; Jaios, Ermansyah; Omar, MH; Abdul Rahman, Suzanah; Hamid, SSA; Ching, Siewmooi; Teh, Lay Kek; Salleh, Mohd Zaki; Darnis, Deny Susanti; Bakhtiar, M. Taher (BioMed Central Ltd, 2016)
Background: Melastoma malabathricum L. (family Melastomaceae) has been traditionally used as remedies against various ailments including those related to pain. The methanol extract of M. malabathricum leaves has been proven to show antinociceptive activity. Thus, the present study aimed to determine the most effective fraction among the petroleum ether- (PEMM), ethyl acetate- (EAMM) and aqueous- (AQMM) fractions obtained through successive fractionation of crude, dried methanol extract of M. malabathricum (MEMM) and to elucidate the possible mechanisms of antinociception involved. Methods: The effectiveness of fractions (100, 250 and 500 mg/kg; orally) were determine using the acetic acid-induced abdominal constriction test and the most effective extract was further subjected to the hot plate- or formalin-induced paw licking-test to establish its antinociceptive profile. Further elucidation of the role of opioid and vanilloid receptors, glutamatergic system, and nitric oxide/cyclic guanosine phosphate (NO/cGMP) pathway was also performed using the appropriate nociceptive models while the phytoconstituents analyses were performed using the phytochemical screening test and, HPLC-ESI and GCMS analyses. Results: PEMM, EAMM and AQMM significantly (p < 0.05) attenuated acetic acid-induced nociception with the recorded EC50 of 119.5, 125.9 and 352.6 mg/kg. Based on the EC50 value, PEMM was further studied and also exerted significant (p < 0.05) antinociception against the hot plate- and formalin-induced paw licking-test. With regards to the mechanisms of antinociception,: i) PEMM significantly (p < 0.05) attenuated the nociceptive action in capsaicinand glutamate-induced paw licking test.; ii) naloxone (5 mg/kg), a non-selective opioid antagonist, failed tosignificantly (p < 0.05) inhibit PEMM’s antinociception iii) L-arginine (a nitric oxide precursor), but not NG-nitro-Larginine methyl esters (L-NAME; an inhibitor of NO synthase), methylene blue (MB; an inhibitor of cGMP), or their respective combination, significantly (p < 0.05) reversed the antinociception of PEMM. Phytochemical analyses revealed the presence of several antinociceptive-bearing bioactive compounds, such as triterpenes and volatile compounds like oleoamide and palmitic acid. The presence of low flavonoids, such as gallocatechin and epigallocatechin, saponins and tannins in PEMM might synergistically contribute to enhance the major compounds antinociceptive effect. Conclusion: PEMM exerted a non-opioid-mediated antinociceptive activity at the central and peripheral levels via the inhibition of vanilloid receptors and glutamatergic system, and the activation of NO-mediated/cGMP-independent pathway. Triterpenes, as well as volatile oleoamide and palmitic acid, might be responsible for the observed antinociceptive activity of PEMM.